Antifertility effect of sulfanilamide on ultrastructure and motility of epididymal spermatozoa in rats - Siriwan Prapong (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
The mechanism of antifertility action of sulfanilamide (SN) was investigated in male rats. Fertility was markedly reduced 5 weeks after oral feeding with 450 mg/kg daily sulfanilamide. However, at week-6 of treatment, the weights of testes and accessory sex organs, i.e. seminal vesicles and coagulating glands were not altered. On the other hand, the weight of the epididymis was significantly decreased. Interestingly, the number of spermatozoa in ejaculates of SN-treated rats was decreased one hundred folds when compared to those of control rats, whereas a slight but significant reduction in the concentration of spermatozoa in the cauda epididymidis was observed. Furthermore, the concentration of cauda spermatozoa with detached head was markedly increased after SN treatment. Vital staining of the cauda sperm also confirmed this finding. Examination by TEM revealed various lesions of the sperm structure including disruption of the sperm plasma membrane producing free exposure of the outer dense fibers to the external environment, disorientation and/or disconnection of the outer coarse fibers and partial disappearance of the dense fibers and/or axonemal microtubules. The highest percentage of damaged spermatozoa was at the cauda epididymidis. In contrast, examinations of testes by light microscope showed normal appearance with all types of cell in the 14 stages of spermatogenesis. On the other hand, sulfanilamide caused decrease in the number of halo cells in the corpus segments. However, there was no significant difference in the relative percentile of the principal cells and clear cells in the three epididymal segments, i.e. caput, corpus and cauda, of both control and SN-treated groups. In addition, this drug also caused depletion of dense granules of the caput epididymal principal cells and caused degeneration of the epididymal principal cells. Per cent motility and curvilinear velocity of both cauda epididymal and ejaculated spermatozoa, analyzed by videomicrography, from SN-treated rats were significantly lower than those of the control after dilution with phosphate buffer saline. When the cauda epididymal spermatozoa from both control and SN-treated rats were cross diluted with prostatic fluid from either control or SN-treated rats, all parameters of sperm motility, i.e. per cent motility, curvilinear and straight-line velocity and linearity index were virtually unchanged. These results suggest that sulfanilamide exerted its antifertility action by mechanisms other than suppression of spermatogenesis, and the results which causing a lesion in sperm structure and motility function could be indirect effect of this drug on epididymal function and perhaps this drug also produced an abnormal ejaculatory process.